Analiza związków pomiędzy wybranymi rynkami kapitałowymi z wykorzystaniem pojęcia przyczynowości w sensie Grangera - Dziekoński, Krzysztof; Tarka, Danuta (Testing of Granger Causality on Selected Capital Markets, 2005)
This paper presents results of the analysis of the potential influence that changes in the DJIA, FTSE100, CAC40 and DAX30 stock market indices can have on the changes in value of polish stock market index WIG20. The results show the dependence of the WIG20 index on the value of DJIA, FTSE100, CAC40 and DAX30. Dependence was considered in accordance with the Granger causality definition. The Granger and Sims-GMW tests were used in the analysis. The analysis was done using daily open and close values of indices under consideration from 1996 till 2003.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 623-631